Employees’ Participation in Management: International Experiences and the Prospects for Canada - Jecchinis, Chris (Relations industrielles / Industrial Relations, 1979)
The experiences of certain successful West European practices in employee's participation within undertaking recommend the establishment of complementary institutional arrangements in the existing system of labour-management relations in Canada which, at the present, is based only on the institution of collective bargaining.